Urology : Manual for teachers preparing for practical classes - Gubar, A. O.; Губарь, Андрій Олександрович (Запорізький державний медичний університет, 2021)
In the manual for teachers in preparation for practical classes, methodological developments for eight topics in the discipline "Urology" according to the work program are collected.